Dampak Sosial Judi Online: Mengguncang Kehidupan dan Keharmonisan dalam Rumah Tangga - Anisa Rahmawati; Nur Azizah; Muhammad Ihsan; Muhammad Azmiannur (Indo Publishing, 2025)
Online gambling has become a phenomenal social phenomenon with various consequences for social life and family. Therefore, the purpose of this study is to analyze the social impact of online gambling practices on family dynamics, especially regarding family cohesion and stability. This study uses several methods, including literature review and qualitative analysis of case studies related to online gambling addiction behavior and its influence on families. In this analysis, indicators underlying these two family elements were identified. The results of this study indicate that online gambling has a negative impact on the family's economic condition, causes interpersonal conflicts, reduces communication levels, and increases the risk of domestic violence and divorce. Furthermore, the addiction resulting from online gambling has led to psychosocial disturbances, such as stress, anxiety, and social isolation, which in turn are responsible for the deterioration of family harmony. Therefore, these findings reinforce support for the primary approach of persuasive intervention and education, along with the addition of social support and responsive policies to enhance family resilience against challenges faced in the digital era.